Research on a suitable upstream traceability model for the natural rubber supply chain in Thailand, specifically for Rib-Smoke-Sheet (RSS) - BEH KOK FONG (Institutional Knowledge at Singapore Management University, 2022)
Traceability is the first step to gain visibility in the supply chain and can be used to meet different purposes. Similar to other agriculture crops, the natural rubber industry faces reputational damage due to deforestation, land grab, loss of biodiversity and non-compliance with environmental standards occurring in the upstream. The introduction of new social and environmental regulations accelerates the need for traceability. Reflecting on the importance of environmental and social considerations, this industry is looking at traceability to identify the historical trends leading to the present sustainability state and any ongoing sustainability risks in the upstream to enable downstream users to formulate responses and actions to mitigate these risks. However, traceability for natural rubber industry is still new and limited research had been conducted in this area. This research focuses on Thailand, world’s largest natural rubber producing country, and their premium product, Rib-Smoke-Sheet (RSS), which is central to tire and car manufacturers. This study identifies the possible depth of traceability up to the closest point of origin in the complex upstream of Thailand Rib-Smoke-Sheet (RSS) and proposes two traceability models that can meet downstream users’ requirements. This research also discusses how downstream users can implement these critical traceability initiatives successfully with supply chain actors; use traceability to formulate responses to sustainability risks; and finally, includes recommendations for future research directions.